2003
DOI: 10.3346/jkms.2003.18.6.881
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Trapdoor Fracture in Children

Abstract: This study was performed to evaluate the clinical symptom, fracture finding, and surgical outcome in children with orbital trapdoor fracture. Forty-four patients with pure orbital trapdoor fracture, under 18 yr of age, were included. Time interval between injury and surgery, length of time for improvement, resolution of ocular motility restriction, and other factors were analyzed in 36 patients who underwent surgery. The median improvement time was 3.5 days for patients (n=8) receiving surgery within 5 days, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…5,[12][13][14] It has been suggested that the timing of paediatric orbital surgery can be classified as immediate (0-48 h), early (3-14 days), and late (15 days or more), with a greater urgency for trapdoor fracture, 18 yet other authors have suggested that early surgery in the paediatric population may include up to several days post-injury. 21 While early treatment of a 'white-eye' orbital floor fracture may not be indicated from the clinical presentation alone, the radiological diagnosis of the trapdoor fracture with entrapped soft tissue/muscle contents may represent a surgical emergency requiring prompt management to avoid a poorer outcome if delayed beyond 48 h. 13,22 The unique nature of 'trapdoor' fractures 4 and the resulting entrapment of adjacent extraocular muscles is also thought to result in a degree of muscle compartment pressure and subsequently ischaemia, as has been described in orthopaedic injuries. 16 Without prompt intervention, muscle ischaemia and/or scarring of the adjacent tissues may lead to impaired ocular mobility with consequent diplopia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…5,[12][13][14] It has been suggested that the timing of paediatric orbital surgery can be classified as immediate (0-48 h), early (3-14 days), and late (15 days or more), with a greater urgency for trapdoor fracture, 18 yet other authors have suggested that early surgery in the paediatric population may include up to several days post-injury. 21 While early treatment of a 'white-eye' orbital floor fracture may not be indicated from the clinical presentation alone, the radiological diagnosis of the trapdoor fracture with entrapped soft tissue/muscle contents may represent a surgical emergency requiring prompt management to avoid a poorer outcome if delayed beyond 48 h. 13,22 The unique nature of 'trapdoor' fractures 4 and the resulting entrapment of adjacent extraocular muscles is also thought to result in a degree of muscle compartment pressure and subsequently ischaemia, as has been described in orthopaedic injuries. 16 Without prompt intervention, muscle ischaemia and/or scarring of the adjacent tissues may lead to impaired ocular mobility with consequent diplopia.…”
Section: Discussionmentioning
confidence: 97%
“…It has been noted that diplopia in patients under 9 years of age takes twice as long to resolve as that in older paediatric patients (10-15 years). 6 Whatever the mechanism of soft tissue injury, early intervention is associated with a superior outcome in trapdoor fractures, 5,14,21 and surgery is therefore recommended within 2 days in this population. 13 It is possible that due to the rapid bone turnover in young patients, early callus formation may make surgical reduction more challenging and contribute to poorer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Baek et al 10 Inferior trapdoor fractures are a common type in children. Yoon et al 24 Surg within 5 days of injury leads to more rapid and better postoperative improvement in patients with severely restricted motility. Kwon et al 25 Diplopia, restricted motility, and trapdoor fractures are more common in children than adults; recovery is faster in children repaired within 5 days of injury.…”
Section: Study Conclusion/recommendationsmentioning
confidence: 97%
“…8,9,12,13,19,20,24,25,31,32 Additional rationale for early intervention includes the fact that patients who present late for surgery are often found to have significant scarring, fibrosis, and callus formation in the fracture area, making adequate reduction of orbital contents difficult. 8,25 Methods of Repair Surgical approaches to repair orbital floor fracture in children are similar to those in adults.…”
Section: Journal Of Aaposmentioning
confidence: 99%
See 1 more Smart Citation